PENINGKATAN AKTIFITAS DAN BERPIKIR KREATIF DALAM PEMBELAJARAN JARING-JARING BANGUN RUANG DENGAN MODEL PROJECT BASED LEARNING DI KELAS V SD NEGERI 130 RANTONATAS - Elvi Elvi (Universitas Negeri Medan, 2018)
Abstract: Increasing Activity and Creative Thinking in Space Build NetworkLearning with Project Based Learning Model in Class V of Public ElementarySchool 130 Rantonatas. The purpose of this study was to describe the increase inactivity and creative thinking of students in learning space-building networks with aproject based learning model. The type of research carried out is classroom actionresearch conducted in two cycles. The research subjects were students of class V atSD Negeri 130 Ranton with a total of 27 students. The research data was obtainedthrough observation sheets, and tests. The data obtained were analyzed qualitatively.The results of data analysis in the first and second cycles showed that students'creative thinking skills improved. In the project based learning process, initiallystudents are not accustomed to conveying ideas and collaborating with otherstudents. However, in the second cycle students have dared to convey ideas andcollaborate in completing the project assignments given. In the first cycle, creativethinking indicators were still in the